Associations with sight-threatening diabetic macular oedema among Indigenous adults with type 2 diabetes attending an Indigenous primary care clinic in remote Australia: a Centre of Research Excellence in Diabetic Retinopathy and Telehealth Eye and Associated Medical Services Network study. Issue 1 (1st July 2021) - Brazionis, Laima; Keech, Anthony; Ryan, Christopher; Brown, Alex; O'Neal, David; Boffa, John; Bursell, Sven-Erik; Jenkins, Alicia
Abstract : Objective: To identify factors associated with sight-threatening diabetic macular oedema (STDM) in Indigenous Australians attending an Indigenous primary care clinic in remote Australia. Methods and analysis: A cross-sectional study design of retinopathy screening data and routinely-collected clinical data among 236 adult Indigenous participants with type 2 diabetes (35.6% men) set in one Indigenous primary care clinic in remote Australia. The primary outcome variable was STDM assessed from retinal images. Results: Age (median (range)) was 48 (21–86) years, and known diabetes duration (median (range)) was 8.0 (0–24) years. Prevalence of STDM was high (14.8%) and similar in men and women. STDM was associated with longer diabetes duration (11.7 vs 7.9 years, respectively; p<0.001) and markers of renal impairment: abnormal estimated Glomerular Filtration Rate (eGFR) (62.9 vs 38.3%, respectively; p=0.007), severe macroalbuminuria (>300 mg/mmol) (20.6 vs 5.7%, respectively; p=0.014) and chronic kidney disease (25.7 vs 12.2%, respectively; p=0.035). Some clinical factors differed by sex: anaemia was more prevalent in women. A higher proportion of men were smokers, prescribed statins and had increased albuminuria. Men had higher blood pressure, but lower glycated Haemoglobin A1c (HbA1c) levels and body mass index, than women. Conclusion: STDM prevalence was high and similar in men and women. Markers of renal impairment and longer diabetes duration were associated with STDM in this Indigenous primary care population. Embedded teleretinal screening, known diabetes duration-based risk stratification and targeted interventions may lower the prevalence of STDM in remote Indigenous primary care services. Trial registration number: Australia and New Zealand Clinical Trials Register: ACTRN 12616000370404.